D’un jardin, l’autre : jardins collectifs, espaces intimes - Sylvaine Dampierre (In Situ)
I am a filmmaker and my first four documentary films were all shot in gardens and in the company of gardeners. A simple idea was at the origins of this project: for those who make them, gardens depict a centre of the world, and being placed at the centre of the world offers a point of view from which to film it. This collection of four films entitled ‘D'un jardin, l'autre’ (from one garden to another) follows a subjective path. It is not a typological essay but a journey dedicated to meeting people, a walk in the heart of the world. The gardens include a workers’ garden, an insertion ‘back-to-work’ garden, an open garden in the middle of a prison and community gardens in New York. They are all inhabited spaces run through by contradictory currents. They are privileged spaces of intimate fulfilment but they are also governed by the subtle laws of collective use. These gardens are all worlds in themselves, containing the dreams of those who shape them. They are spaces of freedom of expression and action but are also confined spaces. The patient elaboration of their inner order is set against the chaos of the outer world. The garden is created in spite of the outside world, in order to resist it. These films are made from inside gardens and with gardeners, at the centre of their lives. They are made out of the time that passes and the weather that prevails. ‘From one garden to another’ is the result of a long-term project, carried out in gardens located at the heart of the social field. The passion that is to be observed there is echoed in broader notions such as work, confinement, utopia, happiness...